Class, Culture and Recognition: San Farm Workers and Indigenous Identities - Sylvain, Renée (Anthropologica, 2022)
This paper examines the processes of identity formation among contemporary Namibian San. I survey the topic from two perspectives. First, I consider features of the political economic and cultural context that shape the recognition and misrecognition of the San by others; second, I argue that the situation of San generational farm workers in the Omaheke Region present important challenges to received definitions of "class," "culture," "authenticity," and "autonomy," and therefore highlight critical limitations to the fields of recognition for indigenous identities in southern Africa.